Kickapoo, Leavenworth County - Baker, Zach (Kansas State University, The Chapman Center for Rural Studies, 2012)
This essay discusses the founding of the Town of Kickapoo, Kickapoo Township, and examines Kickapoo’s battle with Leavenworth and Delaware for the county seat of Leavenworth County. It details how the loss of this competition caused the slow but steady decline of Kickapoo, culminating in the closing of the post-office in 1910.
Zach Baker, “Kickapoo, Leavenworth County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/79.
Keywords: Buffalo Bill; Catholic mission; Kickpoo Indians; Sacred Heart; Weston; Leavenworth County